2009
DOI: 10.3136/fstr.15.307
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Heating for Solubilization of Polysaccharide and Polyphenol from Soybean Residue (Okara)

Abstract: Okara, a soybean by-product of tofu production, was treated with microwave irradiation in water for solubilization of its components. The solubilization rate increased with increasing temperature and reached higher than 70% around 200℃ with a heating time of 7 min. The main solubilized components were neutral carbohydrates consisting of arabinose and galactose, while the residues were mainly composed of cellulose. LV-SEM images confirmed solubilization of cell wall components. Production of new polyphenolic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 28 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Okara polysaccharides also contain a considerable amount of galacturonic acid. Mateos-Aparicio et al and Tsubaki et al also reported galactose, arabinose and galacturonic acid as the major sugars [ 11 , 13 ]. However, in the study of Mateos-Aparicio et al , a maximum amount of arabinose was present in the cellulose-rich residue (equivalent to OP5), and more xylose existed in the 4 M NaOH fraction [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Okara polysaccharides also contain a considerable amount of galacturonic acid. Mateos-Aparicio et al and Tsubaki et al also reported galactose, arabinose and galacturonic acid as the major sugars [ 11 , 13 ]. However, in the study of Mateos-Aparicio et al , a maximum amount of arabinose was present in the cellulose-rich residue (equivalent to OP5), and more xylose existed in the 4 M NaOH fraction [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…with 1 : 20 of solid : liquid ratio resulted in approximately 70% of solubilization (Tsubaki et al, 2009) (Fig.14). Due to high content of pectic arabinogalactan in soybean residue, the maximum carbohydrate production (24.6% at initial weight basis) was achieved at 160°C and 7 min.…”
Section: Soybean Residuementioning
confidence: 99%
“…Okara polysaccharide and protein were extracted using a previously reported microwave-assisted water extraction technique ( Tsubaki et al, 2009 ). Briefly, raw okara was defatted using hexane and dried overnight.…”
Section: Methodsmentioning
confidence: 99%